Carrier Free O2‐Economizer for Photodynamic Therapy Against Hypoxic Tumor by Inhibiting Cell Respiration. Issue 15 (27th February 2022) - Huang, Jia‐Qi; Zhao, Lin‐Ping; Zhou, Xiang; Liu, Ling‐Shan; Zheng, Rong‐Rong; Deng, Fu‐An; Liu, Yi‐Bin; Yu, Xi‐Yong; Li, Shi‐Ying; Cheng, Hong
Abstract: Abnormal tumor metabolism causes the hypoxic microenvironment, which greatly limits the efficacy of photodynamic therapy (PDT). In this work, a strategy of metabolic reprogramming is proposed to economize O2 for enhanced PDT against hypoxic tumors. The carrier‐free O2 ‐economizer (designated as LonCe) is prepared based on the metabolic antitumor drug of Lonidamine (Lon) and the photosensitizer of chlorin e6 (Ce6). By virtue of intermolecular interactions, Lon and Ce6 self‐assemble into nanosized LonCe with favorable stability and high drug contents. Compared with Ce6, LonCe exhibits an improved cellular uptake and photodynamic property for tumor treatment. Moreover, LonCe is capable of inhibiting cell metabolism and mitochondrial respiration to remit the tumor hypoxia, which would promote reactive oxygen species (ROS) production and elevate the PDT efficacy on tumor suppression. In vivo experiments indicate that intravenously injected LonCe prefers to accumulate at the tumor site for highly efficient PDT regardless of the hypoxic environment. Besides, the self‐delivery LonCe is fabricated without any carriers, which avoids the excipients induced system toxicity and immunogenicity in vivo. This carrier‐free nanomedicine with cell respiratory inhibition mechanism would expedite the development and clinical translation of photodynamic nanoplatforms in tumor treatment. Abstract : A carrier‐free O2 ‐economizer (designated as LonCe) is developed based on the metabolic drug Lonidamine (Lon) and photosensitizer chlorin e6 (Ce6), which can interrupt cell metabolism and depress mitochondrial respiration to remit the tumor hypoxia. Experiments show that LonCe will greatly improve the antitumor effect by O2 ‐economized photodynamic therapy regardless of the hypoxic microenvironment.